Isospin-symmetry breaking in kaon production: The role of charge-symmetry - Giacosa Francesco (EPJ Web of Conferences)
An excess of charged versus neutral kaons has been recently reported by the NA61/SHINE collaboration. Similar excesses were also present in previous experiments, even if with larger errors. Models for hadron productions in heavy ion collisions systematically underestimate the measured charge-toneutral kaon ratio. In this report, we comment on the role of charge-symmetry as a specific isospin transformation. In particular, we show that the ensemble of the initial colliding nuclei being charge-symmetric is sufficient for producing an equal number of charged and neutral kaons in the isospin-symmetry exact limit.